Educational studies in the light of the feminine empowerment and transformation - Bouissou-Bénavail, Christine (Science, society and new technologies series. Education set, 2020)
From the theory-practice couple, there are various ways to approach educational and training issues. Intervention research, reflexive situated action and innovation are some of them. Through the analysis of the author's various experiences - professional and initial training, support for change, organizational assessment, experiential learning, project management - this book explores questions about social or professional contexts and the subjective training of actors. One of the challenges is to understand and challenge phenomena such as the development of autonomy and subsidiarity in changing academic or academic contexts. The book promotes the emergence of an ethical and resilient subjectivity. It will show that storytelling is methodological resources for research-intervention paradigms, support the development of actors and stimulate mobility. The book introduces the hypothesis of an operational principle of the feminine as fluid gender, added value to the collective intelligences of the processes of transformation of education and teaching, in terms of intergenerational transmission and in terms of transferability and Strategic activation of skills between business sectors and intellectual fields. This praxeology reconsiders organizations, temporalities, frames of reference, relaunches a reflection in action at the heart of structuration-transformation projects in governance of public action, as well as in terms of personal and collective encapacitation. The reflection opens to questions of management of conflictualities and management of the subjective, epistemological and professional economies.